Brassiere needs of selected flat-chested Filipino women - Sebastian, Paulina Anna Maria G.; Lumawig, Maria Josephine Trono (Quezon City College of Home Economics, University of the Philippines Diliman, 2014)
ABSTRACT The brassiere is the most close-fitting garment a woman wears as it provides both support and comfort for the breasts, while shaping the female figure. There are various studies on women and their brassieres, but there is little research done on the brassiere needs of women with flat-shaped breasts. This study aimed to identify the motivations of flatchested Filipino women in wearing brassieres, common concerns they have regarding brassieres, purchase factors they consider, and their current practices in addressing their needs. The study used descriptive method of research using quantitative and qualitative measures through focus group discussion, interviews, and survey questionnaires. A total of 77 participants aged 18-30 years were selected using chain referral sampling. From the gathered data, the results showed that flat-chested women are motivated by modesty, immodesty, adornment, and protection when wearing brassieres and no single motivation can clearly explain why women, particularly flat-chested Filipino women, wear brassieres. The results also revealed that bra cups are the biggest problem area for flat-chested women, with gapping as the main concern. The results also showed that comfort and fit are among the top factors considered during brassiere purchase. Other factors are support, practicalities, aesthetics, and psychological factors, with certain considerations linked to age. The general sentiment of Filipino women with flat-shaped breasts is that there is a limited selection of bras for them and that the market should widen the range of available choices, especially in terms of size and style. In light of present findings, the bra is still the preferred undergarment for Filipino women with small breasts, despite perceptions of a market gap. Further research on improving products and sizing, as well as extensive exploration of brassiere needs of women, are recommended to improve the selection of undergarments available in the market.
Thesis (B.S. Clothing Technology)--University of the Philippines Diliman.
Keywords: Brassieres -- Philippines